Crashing Project Evaluation by Managing Allocation Resource and Cost using CPM-PERT and MS,Project in Nurul Hayat Mosque’s Renovation - Athira , Nur Rizka; Andris, Dea Ayu Maharani; Khoiroh, Siti Muhimatul (Tibuana, 2021)
The implementation of project management must be calculated based on time and cost estimation. One of the efficiency measures that can take is to accelerate. Time, cost, and quality are factors that must consider while making project acceleration. Project renovation in Nurul Hayat's room was chosen in this research because this project experienced delays in implementation. Delays occur due to a lack of available manpower. This delay will certainly have an impact on costs. The purpose of this research is to speed up time and get optimum costs while still paying attention to quality standards. By CPM-PERT approach, and the evaluation of project acceleration with Ms. Project, the results obtained are scheduling the initial completion of the mosque renovation which initially has an estimated 42 days with a normal total cost of 17,227,500, can be accelerated for 36 working days with additional processing costs of Rp. 70,000 and overtime costs of Rp. 1,635,000. The total cost is Rp 18,932,500 Keyword: Crashing Project, CPM-PERT, Ms. Project